Exercise training in children with asthma: a systematic review. Issue 13 (23rd March 2013) - Wanrooij, Vera HM; Willeboordse, Maartje; Dompeling, Edward; van de Kant, Kim DG
Abstract : Exercise can provoke asthma symptoms, such as dyspnoea, in children with asthma. Exercise-induced bronchoconstriction (EIB) is prevalent in 40–90% of children with asthma. Conversely, exercise can improve physical fitness. The purpose of this paper is to provide a systematic review of the literature regarding the effects of exercise training in children with asthma, particularly in relation to: EIB, asthma control, pulmonary function, cardiorespiratory parameters and parameters of underlying pathophysiology. A systematic search in several databases was performed. Controlled trials that undertook a physical training programme in children with asthma (aged 6–18 years) were selected. Twenty-nine studies were included. Training had positive effects on several cardiorespiratory fitness parameters. A few studies demonstrated that training could improve EIB, especially in cases where there was sufficient room for improvement. Peak expiratory flow was the only lung function parameter that could be improved substantially by training. The effects of training on asthma control, airway inflammation and bronchial hyper-responsiveness were barely studied. Owing to the overall beneficial effects of training and the lack of negative effects, it can be concluded that physical exercise is safe and can be recommended in children with asthma. A training programme should have a minimum duration of 3 months, with at least two 60 min training sessions per week, and a training intensity set at the (personalised) ventilatory threshold. Further research is recommended regarding the effects of exercise on underlying pathophysiological mechanisms and asthma control in children with asthma.